P90 Constrictive pericarditis: a rare and challenging diagnosis. (June 2019) - Sundram, Vasanthee; Cooper, Aimee; Cox, Des; Gavin, Patrick; James, Adam; Daly, Edwina
Abstract : Constrictive pericarditis is a rare condition in children and often presents with clinical features unrelated to the heart making diagnosis challenging. It results from scarring leading to inelasticity of the pericardial sac which produces an inability to adapt to volume changes due to a restriction in diastolic filling. The most common causes in the developed world are idiopathic, prior cardiac surgery and chest radiotherapy. In the developing world tuberculosis remains the commonest cause. We herein report an eleven year old boy of Indian ethnicity who attended a Dublin Paediatric Emergency with chest pain and shortness of breath. He was living in Ireland but spent the first five years of his life in India. His vaccinations including BCG were up-to-date. There was no history of contact with Tuberculosis. He was afebrile and had a normal respiratory rate, heart rate and heart sounds. Examination revealed dullness on percussion in the left lower lobe of the lung with tender hepatomegaly. Chest radiograph reported dense consolidation in the left lower lobe with a parapneumonic effusion. He had a low serum albumin and total protein at 22 g/L and 46 g/L respectively and elevated gamma-glutamyl transferase of 80U/L. The patient was treated with intravenous Cefotaxime and oral Azithromycin for possible pneumonia. He remained systemically well but a repeat radiograph taken five days later showed no improvement. Analysis of pleural fluid by thoracentesis indicated a transudative type. He was seen by the Infectious Disease team and all investigations including inflammatory markers were normal. An eye exam was also normal. Chest computed tomography (CT) scan reported mild pericardial thickening with hepatic enlargement. A large left-sided pleural effusion with minor basal atelectasis and a small contralateral pleural effusion was noted. There was small mediastinal lymphadenopathy. Electrocardiogram (ECG) showed flattening of the T-waves and was generally low voltage. Echocardiogram revealed dilated inferior vena cava and hepatic veins with thickened pericardium and intra-atrial septum deviating towards the Left Atrium suggesting elevated Right Atrial pressure. Cardiac catheterisation demonstrated elevated pressures consistent with constrictive pericarditis. The patient has been taken over by the cardiology team for ongoing management. Discussion: Constrictive Pericarditis is a rare condition in children but this case highlights the importance of a meticulous and multidisciplinary approach to look at other causes when a patient is not responding to treatment as expected.